Effects of Passive Immunization by Anti-Gingipain IgY on the Oral Health of Cats Fed Kibble Diets - Oba, Patricia Massae; Devito, Fernanda Correa; Fernandes Santos, Joao Paulo; Stipp, Rafael Nobrega; Sampaio Gomes, Marcia de Oliveira; Carciofi, Aulus Cavalieri [UNESP]; Brunetto, Marcio Antonio (Sage Publications Inc, 2018)
Porphyromonas gulae is one of the key microorganisms in biofilm dysbiosis that leads to periodontal disease, a prevalent disease in cats. Gingipains are proteases secreted that promote the disruption of cell adhesion and the differentiation of osteoclasts. The use of anti-gingipain immunoglobulin Y (IgY-GP) has emerged as a promising alternative to conventional prevention and treatment methods. The aim of this study was to evaluate the efficacy of IgY-GP on different parameters related to oral health in cats. Twenty adult mixed-breed cats were divided into 2 groups of 10 cats fed with 2 extruded diets differing only by coating. The control group received a coating of 4 g/kg of powdered egg and the test group received a coating of 4 g/kg of IgY-GP. The experiment followed a crossover design with 2 periods, each lasting 40 days with a washout period of 30 days. The evaluated parameters were plaque, calculus, gingivitis index, and percentage of Porphyromonas gingivalis of the oral cavity (%PG-OC) at baseline and after 40 days of diet consumption. All cats remained healthy throughout the study and no adverse reactions or side effects were observed. After 40 days of IgY-GP consumption, the plaque index was significantly lower compared to the baseline (P = .0133). There were no significant changes in calculus index, gingivitis index, and %PG-OC between groups after 40 days (P > .05). The consumption of IgY-GP reduces plaque accumulation, which may lead to an improvement in the oral health of adult cats.
Keywords: feed additive; feline; immunotherapy; oral microbiota; periodontal disease